Transcription, organization, and sequence of an auxin-regulated gene cluster in soybean. - McClure, B A (1989)
We have characterized a soybean gene cluster that encodes a group of auxin-regulated RNAs (small auxin up RNAs). DNA sequencing of a portion of the locus reveals five homologous genes, spaced at intervals of about 1.25 kilobases and transcribed in alternate directions. At least three of the genes are transcriptionally regulated by auxin. An increase in the rate of transcription is detected 10 min after application of auxin to soybean elongating hypocotyl sections. Each of the genes contains an open reading frame that could encode a protein of 9 kilodaltons to 10.5 kilodaltons. Sequence comparisons among the five genes reveal several areas of high homology. Two regions of high homology begin about 250 base pairs upstream of the open reading frames and two regions of homology have been identified in sequences downstream of the open reading frames. One of the latter sequences occurs in the 3'-untranslated region of the RNAs. The other occurs far downstream, 618 base pairs to 741 base pairs from the stop codon. Conservation of these sequences among the five different genes suggests that they may be important for the regulation of expression of the genes.